2018
DOI: 10.1038/s41598-018-19263-8
|View full text |Cite
|
Sign up to set email alerts
|

Periconception onset diabetes is associated with embryopathy and fetal growth retardation, reproductive tract hyperglycosylation and impaired immune adaptation to pregnancy

Abstract: Diabetes has been linked with impaired fertility but the underlying mechanisms are not well defined. Here we use a streptozotocin-induced diabetes mouse model to investigate the cellular and biochemical changes in conceptus and maternal tissues that accompany hyperglycaemia. We report that streptozotocin treatment before conception induces profound intra-cellular protein β-O-glycosylation (O-GlcNAc) in the oviduct and uterine epithelium, prominent in early pregnancy. Diabetic mice have impaired blastocyst deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 62 publications
2
28
0
1
Order By: Relevance
“…The only previous attempt to elevate O-GlcNAcylation in pre-implantation embryos used the alternative OGA inhibitor PUGNAc [ 26 ], which is known to exhibit off-target effects [ 47 ]. In common with our study, Pantaleon et al also used immunostaining with RL2 anti-O-GlcNAcylated protein antibody and showed nuclear and nuclear membrane localisation, as did more recent studies [ 27 , 28 , 29 ]. These localisations likely reflect a concentration of O-GlcNAcylated proteins in nuclear pore complexes [ 48 ], which play important roles in early embryogenesis [ 27 , 28 ], and among DNA-associated proteins such as transcription complexes and histones [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The only previous attempt to elevate O-GlcNAcylation in pre-implantation embryos used the alternative OGA inhibitor PUGNAc [ 26 ], which is known to exhibit off-target effects [ 47 ]. In common with our study, Pantaleon et al also used immunostaining with RL2 anti-O-GlcNAcylated protein antibody and showed nuclear and nuclear membrane localisation, as did more recent studies [ 27 , 28 , 29 ]. These localisations likely reflect a concentration of O-GlcNAcylated proteins in nuclear pore complexes [ 48 ], which play important roles in early embryogenesis [ 27 , 28 ], and among DNA-associated proteins such as transcription complexes and histones [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Current evidence suggests that O-GlcNAcylation downstream of the HBP is required for embryonic genome activation and specification of the TE lineage, through regulation of nuclear localisation of tricarboxylic acid enzymes and Yes-associated protein 1 (YAP1), respectively [ 27 , 28 ]. However, a recent study reported that the increased O-GlcNAcylation observed in blastocysts and endometrium of a mouse model of diabetes is associated with reduced implantation [ 29 ]. Furthermore, placental O-GlcNAcylation is increased in response to stressors such as noise, restraint or disturbance during early gestation, giving rise to altered offspring growth and behaviour [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Embryos from diabetic mothers display exacerbated DNA damage, evidenced by the co - localization of H2AX. O- GlcNAcylation was observed in diabetic blastocyst-stage embryos, favoring impairment of pre-implantation embryo development ( Brown et al, 2018 ). That precursors coming from the metabolic flux have the ability to modulate nuclear function has been denominated metaboloepigenetics ( Donohoe and Bultman, 2012 ); this mechanism provides evidence for an epigenetic contribution to the vertical transmission of diabetes.…”
Section: O- Glcnac During Pregnancymentioning
confidence: 99%
“…Reduced embryo implantation and impaired blastocyst development was observed in an experimental mouse model of diabetes. These findings were related to an inflammatory imbalance, elicited by increased expression of pro-inflammatory cytokines in the uterus, including IL-1α, TNF-α, and interferon gamma (IFNγ), and a pronounced reduction of anti-inflammatory regulatory T-cells within the uterus-draining lymph nodes ( Brown et al, 2018 ).…”
Section: O- Glcnac During Pregnancymentioning
confidence: 99%
“…Self-rated health is measure of general health with the response items of "excellent," "very good," "good," "fair," or "poor." The conditions included in the analysis have been associated with potential pregnancy complications and fetal health [33][34][35][36].…”
Section: Methodsmentioning
confidence: 99%